Intratracheal administration of a nanoparticle-based therapy with the angiotensin II type 2 receptor gene attenuates lung cancer growth - Kawabata, Atsushi; Baoum, Abdulgader; Ohta, Naomi; Jacquez, Stephanie; Seo, Gwi-Moon; Berkland, Cory; Tamura, Masaaki (My University, 2012)
Targeted gene delivery, transfection efficiency and toxicity concerns remain a challenge for effective gene therapy. In this study, we dimerized the HIV-1 TAT peptide and formulated a nanoparticle vector (dTAT NP) to leverage the efficiency of this cell penetrating strategy for tumor-targeted gene delivery in the setting of intratracheal administration. Expression efficiency for dTAT NP-encapsulated luciferase or angiotensin II type 2 receptor (AT2R) plasmid DNA (pDNA) was evaluated in Lewis Lung carcinoma (LLC) cells cultured in vitro or in vivo in orthotopic tumor grafts in syngeneic mice. In cell culture, dTAT NP was an effective pDNA transfection vector with negligible cytotoxicity. Transfection efficiency was further increased by addition of calcium and glucose to dTAT/pDNA NP. In orthotopic tumor grafts, immunohistochemical analysis confirmed that dTAT NP successfully delivered pDNA to the tumor, where it was expressed primarily in tumor cells along with the bronchial epithelium. Notably, gene expression in tumor tissues persisted at least 14 days after intratracheal administration. Moreover, bolus administration of dTAT NP-encapsulated AT2R or TRAIL pDNA markedly attenuated tumor growth. Taken together, our findings offer a preclinical proof of concept for a novel gene delivery system that offers an effective strategy for locally administering lung cancer gene therapy.
Keywords: Angiotensin II type 2 receptor; Cationic peptide nanoparticles; Lung adenocarcinoma; Targeted gene therapy; Apoptosis; Transfection